Zhodnocení výhodnosti užití zpětného leasingu investice financované dlouhodobým úvěrem - Váhalová, Marta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato práce je zaměřena na zhodnocení výhodnosti užití zpětného leasingu investice financované dlouhodobým úvěrem. Pozornost je nejprve věnována podstatě úvěru, leasingu a současnému stavu leasingového trhu v ČR. Cílem snažení je porovnání variant zpětného leasingu jako zdroje financování.

The master’s thesis is aimed at the expedience evaluation of use of a reverse leasing of investment financed by a long credit. First of all the fundamentals of a leasing, a long credit and the present state of the Czech leasing market are reviewed. The target of the effort is the comparison of several reverse leasing’s options as a source of financing.
Expedience evaluation of use of reverse leasing of investment financed by long credit
Keywords: daňová úspora; dlouhodobý úvěr; finanční analýza; leasingová legislativa; leasingová splátka; leasingový koeficient; odpisy; pohyblivá úroková sazba; predikce; splátkový kalendář; spořící splátka; umělá neuronová síť; zpětný leasing; tax saving; long credit; financial analysis; lease legislature; lease instalment; lease coefficient; taxes depreciation; floating rate; prediction; time table for repayment; saving instalment; artificial neuron network; reverse leasing